Chest Radiographs Sensitivity and Specificity of Emergency in the Emergency Department - Munirah Abdulaziz Altowaim, Hind Faisal Almutairi, Feras Ali Alfuzan, Aljoharah Saleh Aldalbhi, Hamed Bader Almutairi, Fahad Bader Almutairi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The interpretation of chest radiographs in the emergency department (ED) presents a challenge due to the complexity of this imaging modality. Previous research has demonstrated substantial discordance between interpretations by clinical physicians and expert radiologists. This discordance underscores the need for comparative analysis between interpretations made by ED physicians and senior radiologists, particularly concerning discharged patients. Evaluating misinterpretations in relation to physician training levels provides insights into the potential impact of expertise on interpretation accuracy.Methods: A prospective review was conducted on radiological descriptions of 509 chest radiographs from 507 discharged ED patients, aged 16–98 years. Missed findings were documented, considering the physician's level of training and experience. Furthermore, the repercussions of misinterpretations on discharge recommendations were explored. Statistical analysis involved the utilization of the χ2 test, while interobserver agreement was assessed using the κ coefficient.Results: Sensitivity for detecting various abnormalities ranged from 20% to 64.9%, with specificities ranging from 94.9% to 98.7%. Despite the observed low sensitivities, the clinical implications of "missed" findings were relatively minor, often resulting in appropriate follow-up recommendations. The overall interobserver reliability, as indicated by the κ coefficient (0.40, 95% confidence interval 0.35 to 0.46), remained consistent across different levels of emergency department physician training.Conclusions: Emergency department physicians frequently overlook specific radiographic abnormalities, highlighting a notable discordance with interpretations by trained radiologists. These findings underscore the importance of routine radiologist evaluation of chest radiographs in the ED setting. Additionally, they emphasize the necessity of enhancing interpretive skills among emergency department physicians to minimize diagnostic discrepancies and optimize patient care.